PENGARUH PROGRAM SAMDES TERHADAP KEPATUHAN WAJIB PAJAK DENGAN KEPUASAN KUALITAS PELAYANAN SEBAGAI VARIABEL INTERVENING - Susilowati , Wahyu Tri; Winarno, Wing Wahyu (Jurnal Riset Akuntansi & Keuangan, 2023)
The purpose of this study was to determine the effect of the SAMDES program on motor vehicle tax compliance through service quality satisfaction as an intervening variable in Bantul Regency. This study uses primary data. The test equipment used in this study was WARP-PLS with 170 respondents.The sampling method used was purposive sampling with the criteria of Bantul vehicle taxpayers both male and female, taxpayers aged between 17 to 60 years, taxpayers who have motorized vehicles and are registered at the Regional Tax Service Office (KPPD) Bantul Regency . The results of the study prove that the SAMDES program has a significant positive effect on motor vehicle tax compliance, service quality satisfaction has no effect on motor vehicle tax compliance, the SAMDES program has a significant positive effect on service quality satisfaction, service quality satisfaction cannot mediate the effect of the SAMDES program on taxpayer compliance motor vehicle.